Screening and oenological property analysis of ethanol-tolerant non-Saccharomyces yeasts isolated from Rosa roxburghii Tratt - Li, Yinfeng; Ding, Peipei; Tang, Xiaoyu; Zhu, Wenli; Huang, Mingzheng; Kang, Mei; Liu, Xiaozhu (Frontiers in Microbiology, 2023)
Ethanol tolerance is crucial for the oenological yeasts. Rosa roxburghii Tratt (R. roxburghii), a Rosaceae plant native to China, is rich in nutritional and medicinal ingredients. In this study, ethanol-tolerant non-Saccharomyces yeasts were screened, and their oenological properties were further evaluated. Three ethanol-tolerant yeast strains (designated as C6, F112, and F15), which could tolerate 12% (v/v) ethanol treatment, were isolated from R. roxburghii, and identified as C. tropicalis, P. guilliermondii, and W. anomalus, respectively. The winemaking condition tolerances of these ethanol-tolerant yeast strains were similar to those of S. cerevisiae X16. However, their growth, sugar metabolic performance, sulphuretted hydrogen activities, and β-glucosidase production were different. Electronic sensory properties of the R. roxburghii wines fermented using ethanol-tolerant yeasts together with S. cerevisiae showed no significant differences. However, the mixed inoculation of the ethanol-tolerant yeast strains with S. cerevisiae could regulate the volatile aroma characteristics of the fermented R. roxburghii wine, enriching and enhancing the aroma flavor. Therefore, the selected ethanol-tolerant yeasts have the potential for application in the production of unique R. roxburghii wine.